2021
DOI: 10.1038/s41598-021-98074-w
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal features and properties of chitosan/sandalwood oil Pickering emulsion coating stabilized by appropriate cellulose nanofiber dosage for fresh fruit application

Abstract: A novel composite edible coating film was developed from 0.8% chitosan (CS) and 0.5% sandalwood oil (SEO). Cellulose nanofibers (CNFs) were used as a stabilizer agent of oil-in-water Pickering emulsion. We found four typical groups of CNF level-dependent emulsion stabilization, including (1) unstable emulsion in the absence of CNFs; (2) unstable emulsion (0.006–0.21% CNFs); (3) stable emulsion (0.24–0.31% CNFs); and (4) regular emulsion with the addition of surfactant. Confocal laser scanning microscopy was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…[28,29,[47][48][49] Various Pickering emulsion systems, which were prepared by using nanocellulose, nanochitin, and nanochitosan, have been explored by mixing different kinds of particle-stabilized emulsion together or by mixing cellulose-stabilized emulsion with chitosan solution. [19][20][21]50,51] However, most of them were focused on the interfacial behavior of stabilizers or the applications for active coating and targeted delivery. Instead of Pickering emulsion, various hydrogels and films, which are composite materials with cellulose and chitosan, have been applied for evaluating cell cytotoxicity.…”
Section: Cell Assaymentioning
confidence: 99%
“…[28,29,[47][48][49] Various Pickering emulsion systems, which were prepared by using nanocellulose, nanochitin, and nanochitosan, have been explored by mixing different kinds of particle-stabilized emulsion together or by mixing cellulose-stabilized emulsion with chitosan solution. [19][20][21]50,51] However, most of them were focused on the interfacial behavior of stabilizers or the applications for active coating and targeted delivery. Instead of Pickering emulsion, various hydrogels and films, which are composite materials with cellulose and chitosan, have been applied for evaluating cell cytotoxicity.…”
Section: Cell Assaymentioning
confidence: 99%
“…According to the latter considerations, it clearly emerges that the determination of the suitable concentration of cellulosic materials outstands as a pivotal parameter to achieve improved antifungal properties in cellulose-based coatings [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the optimal amount of nanoparticle addition can be determined by evaluating the microstructure of the emulsion and its storage stability (Wardana et al, 2021). Nonetheless, when it comes to food packaging, thoroughly characterizing the properties of films and choosing the optimal nanoparticle concentration is crucial to ensure optimum performance (Figure 2a).…”
Section: Nanoparticles Addition Amountmentioning
confidence: 99%